The Big Gamble : The Migration of Eritreans to Europe (2019)
Why, every year, tens of thousands of people are willing to risk their lives in perilous voyages across Africa and the Mediterranean Sea? Why do they face such an ordeal to reach European countries where their long-term prospects are often dismal? The Big Gamble answers these questions through a multi-sited ethnography with refugees, their families back, smugglers and relatives in the diaspora. By visiting family homes in Eritrea, living with refugees in camps and urban peripheries across Ethiopia, Sudan and Italy, the author untangles everyday challenges as well as images, desires and feelings of young Eritreans pursuing their desired destination in a context of protracted crisis and long-term displacement. Throughout the book the author shows the importance of recognizing the space for choices in contemporary refugee movements. It argues that imagination, morality and emotion are crucial elements to understand the trajectories and the motivations of those who bet not only their resources but also their lives to seek asylum in Europe.